Illness, Identity, and Taboo among Australian Paleo Dieters - Gressier, Catie (Springer International Publishing, 2018)
This book explores the cultural and economic conditions fuelling the popularity of the polarizing Paleo diet in Australia. Based on ethnographic research in Melbourne and Sydney, Catie Gressier recounts the compelling narratives of individuals struggling with illness and weight issues. She argues that 'going Paleo' provides a sense of agency and means of resistance to the neoliberal policies and practices underpinning the growing prevalence of lifestyle diseases. From its nostalgic constructions of the past, to the rise of anti-elite sentiments inherent in new forms of health populism, Gressier provides a nuanced understanding of the Paleo diet's contemporary appeal.